Influence of di(2-ethylhexyl) phthalate on dysregulation of testosterone production via alteration of aromatase expression: Influence of di(2-ethylhexyl) phthalate on testosterone - Park, Min Ju; Lee, Seung Ju; Park, Yong Joo; Yoo, Eunsoo; Kim, Hye Kyung; Park, Min Hi (Cellular and Molecular Biology, 2025)
Di(2-ethylhexyl) phthalate (DEHP), an endocrine-disrupting chemicals (EDCs), is commonly used as a plasticizer to improve the flexibility and durability of plastics. On a daily basis, we are exposed to varying amounts of this compound. Several studies have demonstrated that exposure to DEHP and its metabolite, mono(2-ethylhexyl) phthalate (MEHP), leads to testosterone deficiency (TD) in both humans and animals. However, the precise mechanism that causes DEHP-induced TD is still not completely understood. This study aims to determine the effects of DEHP on testosterone levels and elucidate the underlying mechanisms. C57BL/6 mice and Leydig cells were exposed to various doses of DEHP (0, 0.5, and 5 mg/kg/day) for 9 weeks and MEHP (0, 0.05, 0.5, and 5 μM) for 24 hours, respectively. Both in vivo and in vitro results indicated significant reductions in testosterone levels due to DEHP and MEHP. Additionally, DEHP and MEHP increased the expression of aromatase, a gene that converts testosterone to estradiol and induced an increase in the expression of inflammatory cytokines such as IL-6, IL-1β, and TNF-α. Moreover, DEHP activated NF-κB, a key transcription factor regulating numerous genes associated with inflammation. These results suggest that sustained exposure to DEHP increases inflammatory factors, which may elevate aromatase activity and result in decreased testosterone levels in the body. Furthermore, this study provides a basis for discussing the potential correlation between persistent DEHP exposure and TD characterized by low testosterone levels in the body.